Modelling the quasistatic crack propagation in a viscoelastic orthotropic medium using the incrementalization of constitutive equations - Selivanov, M.F.; Fernati, P.V. (Reports of the National Academy of Sciences of Ukraine, 2023)
The algorithm for modelling the process of creep crack in a viscoelastic media is discussed in this paper. The algorithm combines the viscoelastic incremental formulation and procedure of quasistatic fracture modelling; it is implemented by the finite element method and illustrated by the numerical example of determining a change with time of a stressed state in the vicinity of the failure zone. The cohesive zone model with nonuniform traction– separation law is used as a crack model that accounts for the failure zone at a crack tip. The deformational criterion is chosen to define a crack critical state. The growth of an edge crack in a viscoelastic orthotropic plate with relaxation moduli defined by a single exponential function is illustrated in the numerical example. The close-to- uniform traction–separation law of smoothed trapezoidal form is used within the cohesive zone model approach and satisfied for each discrete moment which is found by the proposed algorithm given the current crack geometry.